The future of e-commerce in the publishing industry - Yousef A. Baker, El-Ebiary; Julaily Aida, Jusoh; Khairi, Aseh; Omar Mohammed Ali, Abdullah Al-Qudah; M Hafiz, Yusoff; Pathmanathan, P.R.; Nurul Adilah, Abdul Latiff; Waheeb, Abu-Ulbeh; Yazeed, Al Moaiad (2021)
In comparison to conventional book-printed content, electronic " publishing "has allowed users to import files to either a personal computer or an e -book reader to read text in a digital format. Reduced printing costs and reduced time to market by streamlined drafting, proofing, and printing methods are the benefits of the publishing industry over the conventional printed book (p-book). It prevents binding, distribution and shipping. The intent of this paper is to explore the strategic use of e - commerce in the transformation of the publishing industry . The first part of the paper discusses the strategic use of e - commerce /Web-Based Business in the transition from a single distribution channel mass producer of printed books to a multiple distribution channel that will include e -books and print on demand technology in the publishing industry . Emphasis is put on management techniques in the global marketplace for the use of emerging information technologies. The second section of this paper addresses the transfer in competitive influence between the different levels of the supply chain of the publishing industry , including the latest trends in electronic publishing from the stakeholders' point of view. Expected to serve as the base for development within the digitized print industry . As e - publishing becomes popular and moves towards maturity, to allow a "mainstream"status, common standards must emerge and combine.